Bone physiological adaptations to whole-body vibration in mouse models: A Systematic Review - Roberto Bonanni; Ida Cariati; Lucio Caprioli; Cristian Romagnoli; Angela Falvino; Saeid Edriss; Pierangelo Cifelli; Giovanna D’Arcangelo; Elvira Padua; Virginia Tancredi; Giuseppe Annino (PLoS ONE, 2026)
Whole-body vibration (WBV) is known to mechanically stimulate bone tissue, modulating its turnover and microarchitecture. Our systematic review aimed to collect the available evidence on the effects of WBV in mouse models, comparing the different experimental protocols and results obtained. A systematic literature search was conducted in the MEDLINE, Scopus, and Web of Science databases, in accordance with PRISMA guidelines. Experimental studies investigating the effects of WBV on healthy mice of different age groups, models of osteoporosis or fracture healing, and other models of bone loss were included. Methodological quality was assessed using SYRCLE’s RoB tool to analyze the reliability of the results and the risk of bias and the adapted GRADE approach to determine the overall level of certainty of the evidence. Twenty-nine studies were included, of which 10 were on healthy mice, 9 on osteoporotic or fracture healing models, and 10 on other models of bone loss. Overall, WBV improved bone formation, mineral density, and trabecular and cortical microarchitecture, although the results were heterogeneous and dependent on frequency, acceleration, duration, and recovery times. In some models, WBV combined with parathyroid hormone (PTH) or oestrogen showed synergistic effects, while in disuse and metabolic models, mechanical vibrations preserved bone mass and reduced osteoclastic activity. WBV represents a potentially useful strategy for modulating bone turnover and improving density and microarchitecture, with effects strongly influenced by protocol parameters and pathophysiological status. Further studies are needed to clarify the mechanisms, optimize protocols, and evaluate the clinical impact in different study populations.